The Effect of Work-Family Conflict, Work Environment, Work Stress, Job Satisfaction on High and Low Employee Performance at the Faculty of Medicine, Udayana University - Purnama Dewi, I Gusti Ayu; Sanica, I Gede (Universitas Ibn Khladun Bogor, 2023)
In an organization, performance is very important to determine the success of the organization. Performance can be interpreted as work results that can be achieved by an employee or a group of employees in order to achieve organizational goals. Therefore, it is necessary to conduct research on the factors that influence employee performance, so that steps can be taken to improve their performance. Factors that affect employee performance are work family conflict, work environment, job stress, and job satisfaction. This study aims to analyze the factors that affect employee performance, namely work-family conflict, work environment, job stress, and job satisfaction. The method used in this study is a quantitative method. The sample used was 131 respondents. The data collection tool uses a questionnaire distributed through the Google form. The method used is the analysis of alternative structural equation models (SEM) with the PLS method using the SmartPLS 3.0 program. The results showed that there was a positive influence between work environment variables and job satisfaction on employee performance p<0.05. Meanwhile, the work family conflict and work stress variables have a negative effect on employee performance with p <0.05. Implication: the results of this study are expected to be able to contribute to organizations or companies in improving employee performance The results showed that there was a positive influence between work environment variables and job satisfaction on employee performance p<0.05. Meanwhile, the work family conflict and work stress variables have a negative effect on employee performance with p <0.05. Implication: the results of this study are expected to be able to contribute to organizations or companies in improving employee performance The results showed that there was a positive influence between work environment variables and job satisfaction on employee performance p<0.05. Meanwhile, the work family conflict and work stress variables have a negative effect on employee performance with p <0.05. Implication: the results of this study are expected to be able to contribute to organizations or companies in improving employee performance